2021
DOI: 10.31822/jomat.2021-6-2-73
|View full text |Cite
|
Sign up to set email alerts
|

Marketing cheese tourism in global times

Abstract: Food tourism is defined as a journey to a destination in order to discover a culture through its food. Special segments of culinary tourism have emerged during the last decades to valorize local products and drinks and award tourism value to food. This is the case of cheese tourism, which has been recently studied with increasing management and marketing implications. In this sense, planning and development of food-based marketing strategies represent a key factor towards the success of a niche tourism. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This study revealed that the most valued teaching methodologies and activities are those that directly involve students and promote direct visits to the natural environment [35,41,62,63,91,92]. Specifically, the results showed a vivid interest in experiencing the gastronomic culture, which reveals the importance of sensory experiences in the appreciation and understanding of the rural environment and its traditions [49,52,[93][94][95].…”
Section: Discussionmentioning
confidence: 97%
“…This study revealed that the most valued teaching methodologies and activities are those that directly involve students and promote direct visits to the natural environment [35,41,62,63,91,92]. Specifically, the results showed a vivid interest in experiencing the gastronomic culture, which reveals the importance of sensory experiences in the appreciation and understanding of the rural environment and its traditions [49,52,[93][94][95].…”
Section: Discussionmentioning
confidence: 97%
“…Market segmentation has encouraged the creation of new tourism products centered on gastronomy, where experiences and sensations become especially relevant [64]. Activity 6 (spend a day with a goat, sheep, and/or cow herder and participate in a local breed meat tasting) ranked fourth in average score and attained the highest average score in willingness to pay.…”
Section: Discussionmentioning
confidence: 99%